Maqasid al-Shariah: enhancing well-being through product development process in Islamic banks of Pakistan - Farah Yasser; Altaf Hussain Saqib; Zunera Khalid (Penerbit Universiti Kebangsaan Malaysia, 2024)
The significance of Maqasid in developing innovative and new products and services by Islamic )inancial institutions is undeniable and beyond question, as it not only guides the objectives and goals of Islamic laws but also helps establish a guiding framework for the well-being of the consumers. Therefore, this study is an effort to assess the extent to which Islamic )inancial institutions within Pakistan integrate Maqasid into their product and service development. The data is gathered in two phases, and a mixed method approach is used to achieve the objectives of the current study. The )irst phase is qualitative, where the main themes are built through content analysis using NVivo. Based on the themes built in the )irst phase, a questionnaire is established in the second quantitative phase. Data is collected from banking executives and Shariah advisors who are directly involved in the product development process. The )indings show that Maqasid al-Shariah is acknowledged in Pakistan's Islamic banks' purpose and vision statements. It also concludes that in all three phases of product development, i.e., from idea generation to product conversion and product commercialization, most Islamic banks have considered Maqasid al-Shariah. This study is helpful for customers of Islamic banks, bankers, and society as the products developed after considering Maqasid al Shariah provide justice, equity, and well-being in society.